The Effects of Severe Iron Deficiency Anemia on T-wave Intervals - Findikli, Huseyin Avni; Tutak, Ayse Sahin (Archives of Clinical and Biomedical Research, 2018)
Aim: Changes in the iron level in the myocardium may be affected by sodium and potassium channels in myocytes and there may be a contribution to the etiology of cardiac arrhythmia. The aim of this study was to examine for the first time in literature how the Tp-e interval, which has been accepted in recent years as a strong ventricular repolarisation index, is affected in female patients with severe iron deficiency anemia. Material and Methods: The study included a total of 64 participants, as a study group of 34 patients diagnosed with severe iron deficiency anemia (Hgb<8g/dL Ferritin<14 mcg/L, MCV<80 mm3) and a control group of 34 subjects. To determine the QTc and Tp-Te interval durations, manual examination was made of manual precordial V5 lead ECGs taken routinely on the presentation of all participants. Results: The Tp-e interval was determined to be statistically significantly shorter in the patients (78.97 ± 8.63 ms) compared to the control group (84.57 ± 10.13 ms) (p<0.05). A positive relationship was determined between Tp-e and QTc durations and Hgb and ferritin levels (p<0.05). Conclusion: The results of the study showed that the QTc duration and the Tp-e duration were shorter in female patients with iron deficiency anemia, and therefore iron deficiency anemia can be discounted as a cause of prolonged QTc and Tp-e durations.